Analisis Pengetahuan Investasi terhadap Minat Investasi Saham dengan Persepsi Risiko sebagai Intervening - Ruwaida, Ruwaida (Universitas Darwan Ali, 2024)
The increasing investment education campaigns conducted by PT Bursa Efek Indonesia (BEI) and the availability of Investment Galleries in universities openup great opportunities for students to invest in the capital market. Previous studies have examined the topics of investment knowledge, risk perception, and investment interest. However, previous research still has some shortcomings that need to be improved and developed. These shortcomings include sample size that does not represent the population, the absence of control variables in the research, and some technical shortcomings in the methodology.This study aims to analyze the effect of investment knowledge on the investment interest in stocks of young investors in Kotim with risk perception as an intervening variable. This research uses a quantitative method with cross-section data on 100 young investors at Darwan Ali University. The results of the study show that investment knowledge has a significant positive effect on risk perception and stock investment interest. However, the availability of capital does not show a significant effect on investment interest. These findings highlight the importance of investment education for students and the contribution of risk perception in increasing stock investment interest. This research provides a reference for the development of investment education strategies in the future.